Combined Transcriptome and Metabolome analysis of Pitaya fruit unveiled the mechanisms underlying Peel and pulp color formation - Zhaoxi Zhou; Hongmao Gao; Jianhong Ming; Zheli Ding; Xing’e Lin; Rulin Zhan (BMC Genomics, 2020)
Abstract Background Elucidating the candidate genes and key metabolites responsible for pulp and peel coloration is essential for breeding pitaya fruit with new and improved appeal and high nutritional value. Here, we used transcriptome (RNA-Seq) and metabolome analysis (UPLC-MS/MS) to identify structural and regulatory genes and key metabolites associated with peel and pulp colors in three pitaya fruit types belonging to two different Hylocereus species. Result Our combined transcriptome and metabolome analyses suggest that the main strategy for obtaining red color is to increase tyrosine content for downstream steps in the betalain pathway. The upregulation of CYP76ADs is proposed as the color-breaking step leading to red or colorless pulp under the regulation by WRKY44 transcription factor. Supported by the differential accumulation of anthocyanin metabolites in red pulped pitaya fruit, our results showed the regulation of anthocyanin biosynthesis pathway in addition to betalain biosynthesis. However, no color-breaking step for the development of anthocyanins in red pulp was observed and no biosynthesis of anthocyanins in white pulp was found. Together, we propose that red pitaya pulp color is under the strict regulation of CYP76ADs by WRKYs and the anthocyanin coexistence with betalains is unneglectable. We ruled out the possibility of yellow peel color formation due to anthocyanins because of no differential regulation of chalcone synthase genes between yellow and green and no detection of naringenin chalcone in the metabolome. Similarly, the no differential regulation of key genes in the carotenoid pathway controlling yellow pigments proposed that the carotenoid pathway is not involved in yellow peel color formation. Conclusions Together, our results propose several candidate genes and metabolites controlling a single horticultural attribute i.e. color formation for further functional characterization. This study presents useful genomic resources and information for breeding pitaya fruit with commercially attractive peel and pulp colors. These findings will greatly complement the existing knowledge on the biosynthesis of natural pigments for their applications in food and health industry.